Bacteria Recovered from Whole-Carcass Rinsates of Broiler Carcasses Washed in a Spray Cabinet with Lauric Acid-Potassium Hydroxide - Hinton, A. Jr.; Cason, J.A.; Buhr, R.J.; Liljebjelke, K. (International Journal of Poultry Science, 2009)
Effects of spray washing carcasses with Lauric Acid (LA)-Potassium Hydroxide (KOH) on bacteria recovered from Whole-Carcass Rinsates (WCR) were examined. Carcass skin was inoculated with antibiotic resistant strains of Escherichia coli, Salmonella Typhimirum and Campylobacter coli. The first trial examined effects of washing carcasses with water, 0.25% LA-0.125% KOH, 0.50% LA-0.25% KOH, 1.00% LA-0.50% KOH, or 2.00% LA-1.00% KOH at 80 psi for 15 sec. Findings indicated that significantly fewer Total Plate Count (TPC) bacteria, E. coli and Salmonella Typhimirum were recovered from carcasses washed with 2.00% LA-1.00% KOH than from carcasses washed with water and that no C. coli were recovered from carcasses washed with 2.00% LA-1.00% KOH. Another trial examined effects of washing carcasses at 60, 100, or 150 psi of pressure with 2.00% LA-1.00% KOH for 15 sec. Findings indicated that significantly fewer TPC bacteria were recovered from rinsates of carcasses washed with 100 psi than from carcasses washed with 60 or 150 psi. Finally, a trial was conducted to examine effects of washing carcasses for 0, 5, 15, or 30 sec with 2.00% LA-1.00% KOH at 100 psi. Results indicated that significantly fewer bacteria were recovered from carcasses washed for 5 sec than from unwashed carcasses. Furthermore, significantly fewer TPC bacteria and Salmonella Typhimirum were recovered from carcasses washed for 15 sec than for 5 sec and no C. coli were recovered from carcasses washed for 15 or 30 sec. Findings indicate that spray washing carcasses with LA-KOH can affect the number of bacteria recovered from WCR. These studies also provide data that may be useful in designing applications for using of microbicidal surfactants in processing operations.